Penerapan Akuntansi Sederhana pada Pengelolaan Dana Koinisasi dan Rosok di LAZISNU Ranting Pagu Kediri - Adinda Ayu Rizkya Putri; Iza Zuharoh; Lia Rahmawati; Lutfi Nur Fianah; Ririn Tri Puspita Ningrum (MONETARIUM: Journal of Economics Business and Management, 2026)
This research seeks to analyze the method of documenting social fund income generated from the Koin NU initiative and the Scrap Donation Movement at the LAZISNU branches located in the MWC NU Wates Kediri region. The investigation centers on assessing how well the recording methods align with PSAK 109 regarding the accounting practices for zakat, infaq, and sadaqah, while also scrutinizing their accountability processes. A qualitative descriptive method was utilized, which included an analysis of financial documents and interviews with the branch managers. The results indicate that the revenue documentation is performed through a straightforward cash basis system, where transactions are noted only when cash is received. Even though there is a routine of reporting and summarizing balances, the branches have not segregated funds according to their categories or created detailed financial statements such as financial position statements and changes in funds as mandated by PSAK 109. These aspects reflect a degree of adherence to accounting guidelines. Although fundraising initiatives driven by the community effectively encourage social engagement, the financial reporting framework remains more focused on administrative tasks than on achieving professional standardization. Therefore, it is crucial to enhance the classification of funds, improve the reporting formats, and implement digital recording methods to increase transparency, accountability, and institutional trustworthiness at the branch level.